Flexural Fatigue Behavior of Reinforced Concrete Beams Strengthened with Fiber-Reinforced Polymer Grid-Reinforced Engineered Cementitious Composite Matrix Composites - Zheng, Aohan; Wang, Siyu; Lu, Yiyan; Li, Shan (ACI structural journal, 2022)
In this study, the flexural fatigue performance of reinforced concrete (RC) beams strengthened with a fiber-reinforced polymer (FRP) grid-reinforced engineered cementitious composite (ECC) matrix was experimentally investigated. An FRP grid-reinforced ECC matrix (FGREM) composite strengthening layer was applied by reinstating the original concrete layer to a predetermined depth. The load level, FRP grid type, and strengthening amount were considered as test variables. The ultimate fatigue failure of the strengthened beams was found to be governed by the fracture of tensile steel bars. However, premature end debonding could be triggered in specimens subject to excessive strengthening. Furthermore, the fatigue life of the strengthened beams was distinctively improved owing to the relieved tensile stress range of the steel reinforcements. By relieving the damage accumulation of the constituent materials, this strengthening system can effectively ameliorate cracking, which is of great significance to the degeneration of stifness and the development of deflections. Keywords: engineered cementitious composite (ECC); fatigue loading; fiber-reinforced polymer (FRP) grid; flexural performance; reinforced concrete (RC) beam; strengthening.